Upaya Konservasi Lingkungan Kampus melalui Gerakan Penanaman Pohon untuk Mewujudkan Green Campus - Rodji, Achmad Pahrul; Artiani, Gita Puspa; Sukadi, Sukadi; Indriasari, Indriasari; Zatmika, Ajat; Sutaryo, Sutaryo; Khuluk, Nazaruddin; Andiani, Tiara; Kurniawan, Aisyahqi Ramadhani Putri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The increase in pollution and micro temperatures within the Universitas Krisnadwipayana (UNKRIS) campus environment requires concrete solutions through the optimization of green open spaces. This community service aims to reforest the campus while strengthening local food security by planting productive trees. The methods used include community education on environmental conservation, planting technique training, and science and technology diffusion through the planting of 50 Multipurpose Tree Species (MPTS) seedlings, such as miki avocado, arumanis mango, breadfruit, citra water apple, and citrus. The results show a significant increase in academic community awareness and improvement in the campus's physical environmental quality. Collaboration with agricultural experts ensures the sustainable growth of the plants. In conclusion, the integrated planting of shaded and productive trees creates a cooler and more food-independent campus ecosystem. This activity is vital as a pilot model for educational institutions in supporting the sustainable development agenda and collective responsibility for earth's sustainability.